Careers in Nigeria - Okam, Eric C. N. (London : Evans Brothers, 1966)
"Careers in Nigeria" has been written primarily to help young people in their choice of employment and to assist teachers, parents, guardians, employment officers and all those whose duty it is to advise them.
Includes index.
rpm 04/05/2018
Loans
Keywords: Occupations; Vocational guidance; Nigeria